Tracking a drowning unconformity up to the peritidal zone: Proximal expression of the early Bajocian carbonate crisis in Morocco. (October 2021) - Danisch, Jan; Krencker, Francois-Nicolas; Mau, Malte; Mattioli, Emanuela; Fauré, Philippe; Alméras, Yves; Nutz, Alexis; Kabiri, Lahcen; El Ouali, Mohamed; Bodin, Stéphane
Abstract: The early Bajocian environmental crisis is marked by floral and faunal turnovers, and a positive carbon excursion recognized in both marine and continental archives. In the basinal setting of the Central High Atlas Basin, it is concomitant to a drastic drop of carbonate content, interpreted as a result of a severe carbonate demise event in neritic settings. In order to provide a carbonate platform perspective of this demise event, we have investigated a proximal–distal transect consisting of five sections of the Errachidia Platform, which represents upper neritic settings on the southern margin of the basin. New nannofossils and brachiopod findings, supported by organic matter carbon isotope chemostratigraphy, allow for the establishment of a high-resolution chronostratigraphic framework of the Errachidia Platform and a detailed reconstruction of carbonate factory evolution during the late Aalenian to middle Bajocian interval. The early Bajocian (Propinquans Zone) environmental crisis triggered a severe demise event which restricted carbonate production to supra-to intertidal settings, where microbial and peloidal limestones are the only trace of carbonate production. As a consequence, most of the platform is dominated by extended marl deposits that are usually interpreted as hemipelagic deposits. This observation demonstrates that caution must be exerted when interpreting the depositional environments of marl-dominated successions during time of neritic carbonate factory demise. Highlights: Neritic carbonate factory restricted to nearshore environments during drowning event. Characterized by microbial and peloidal limestones. Original biostratigraphic and chemostratigraphic data for the Bajocian of the Central High Atlas. New lithostratigraphic scheme for the Errachidia Platform.